DEVELOPMENT OF A PROJECT-BASED LEARNING E-MODULE FOR RHYTHMIC GYMNASTICS TO IMPROVE CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Imam Santosa; Yudha Febrianta (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Rhythmic gymnastics activities in elementary schools still face limitations in interactive teaching materials that can encourage critical thinking skills. This study aims to develop a Project-Based Learning (PJBL)-based rhythmic gymnastics e-module to improve the critical thinking skills of students at SDN 1 Sokanandi. The study employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of 40 fifth-grade students divided into experimental and control groups. Data were collected through expert validation, critical thinking tests, and documentation, then analyzed using IBM SPSS Statistics 26 through normality tests, homogeneity tests, Mann–Whitney U Test, and effect size analysis. The results showed that the developed e-module was feasible for use, with validation scores of 86% from media experts and 77.78% from material experts. The use of the PJBL-based e-module resulted in better improvement in students’ critical thinking skills compared to conventional learning, as indicated by the Mann–Whitney test results (p < 0.05) with an effect size of 0.68, categorized as a large effect. Therefore, the PJBL-based rhythmic gymnastics e-module is effective as a Physical Education, Sports, and Health (PJOK) learning medium to support the development of students’ critical thinking skills. Teachers can utilize PJBL-based e-modules to promote active and innovative Physical Education